Development of energy harvesting system using rotation mechanism of a revolving door - Gilani, S.F.-H. (Asian Research Publishing Network, 2015)
Conventional energy sources are depleting with time. There is a dire need to find new sources of energy. The new sources of energy should be able to replace dwindling sources of energy. Energy Harvesting is one such method where ambient energy from environment is converted into useful energy. The purpose of this study is to show that the ambient energy in the surroundings can be utilized to generate electricity. In this project, the energy used to open a revolving door is being converted into electrical energy. Accordingly, a revolving door prototype is designed, fabricated and tested. The test results show that 15.67 Joules can be produced from one push of the door. A carbon comparison case study is carried out based on the results. This prototype can be further optimized in terms of size to generate more electrical energy. Â© 2006-2015 Asian Research Publishing Network (ARPN).